New brain lesions in a patient with sarcoidosis: is it neurosarcoidosis? - Pandey, Subodh; Mukhopadhyay, Sanjay; Iannuzzi, Michael C.; Sah, Birendra P (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
A 45-year-old woman with pulmonary sarcoidosis diagnosed 5 years previously, who was on treatment with prednisone and methotrexate for 1year, developed partial seizure with secondary generalization. MRI showed three non-cavitary enhancing lesions in the cerebello-occipital region. These lesions were presumed to be neurosarcoidosis. Methotrexate was discontinued, prednisone dose was increased and azathiopurine and levetiracetam were added. While on treatment, follow up imaging showed enlarging brain lesions. Biopsy of the lesions showed Epstein Barr virus (EBV) positive diffuse B cell lymphoma. Immunosuppressants were tapered off and she was begun on Rituximab. Because of lack of improvement after 4 cycles of Rituximab, she was then treated with high dose Methotrexate and Temozolamide. We present this case as a diagnostic challenge. New enhancing brain lesions occurring in a patient with long standing sarcoidosis, while likely to be neurosarcoidosis, may be due to a complication of immunosuppressant therapy. The need for early biopsy, if the lesions do not improve, should be considered.